Studies on the Effect of Aging and Mesothelioma on Dendritic Cell Subsets - Cornwall, Scott M.J. (Curtin University, 2015)
Mesothelioma is a cancer that occurs in the elderly. Dendritic cells (DC) play a key role in generating immune responses. This thesis examined DCs in elderly mesothelioma patients and reports that numerical and functional defects due to aging were significantly amplified in mesothelioma patients. Whilst CD40 stimulation recued the function of healthy elderly DCs it offered little benefit to mesothelioma DCs. Surgery improved mesothelioma DC function implying a window of opportunity for use of immunotherapies.